Fungi-Based Microbial Fuel Cells - Anna Sekrecka-Belniak; Renata Toczyłowska-Mamińska (Energies, 2018)
Fungi are among the microorganisms able to generate electricity as a result of their metabolic processes. Throughout the last several years, a large number of papers on various microorganisms for current production in microbial fuel cells (MFCs) have been published; however, fungi still lack sufficient evaluation in this regard. In this review, we focus on fungi, paying special attention to their potential applicability to MFCs. Fungi used as anodic or cathodic catalysts, in different reactor configurations, with or without the addition of an exogenous mediator, are described. Contrary to bacteria, in which the mechanism of electron transfer is pretty well known, the mechanism of electron transfer in fungi-based MFCs has not been studied intensively. Thus, here we describe the main findings, which can be used as the starting point for future investigations. We show that fungi have the potential to act as electrogens or cathode catalysts, but MFCs based on bacteria–fungus interactions are especially interesting. The review presents the current state-of-the-art in the field of MFC systems exploiting fungi.